Refracting exoticism in video representations of the victim-refugee: K'Naan, Angelina Jolie and research responsibilities. Issue 2 (1st October 2018) - Goheen Glanville, Erin
Media that makes use of the fixed, two-dimensional victim-refugee figure participates in a kind of exoticization of refugee-ed people by reading forced displacement exclusively through the lens of suffering. Yet the body of scholarship critiquing this media is susceptible to saying more about the scholars and their concerns than about the concerns of those whose experiences are being represented. This article returns to focus group research from 2009 when the author ran media discussion workshops with refugee activists, including both refugee and citizen participants. The workshop discussions focused on K'Naan's hip hop video 'Soobax' and Hollywood film Beyond Borders. The research aimed to understand the pedagogical potential of textual and audio-visual narrations of refugee cultures but became an exercise in refracting the exoticization latent in the project's research questions. One important outcome of this research was the different emphases in participant responses to the victim-refugee figure in the videos. Workshop participants with a refugee background iterated that, given the context of growing apathy and antipathy towards refugee claimants in Canada, the representation of refugees as suffering victims remains a useful and powerful intervention in public debates. The article finishes with some reflections on the implications of the research findings and on the responsibility of engaged scholarship for researchers in cultural refugee studies and humanitarian communication.